Monitoring and Evaluation of the Tun Abdul Razak 3 Library Based on the EUCS Model - Shah Rullnizam, Amal Faiqah (Universitas Pendidikan Indonesia, 2021)
Library research is research conducted by using libraries, such as books, notes, or reports on past research results. A qualitative causality study was conducted as part of the study. The aim is to obtain information about the criteria for librarians and head of librarianship, obtain feedback on the satisfaction of library users, identify problems faced by users with the collections or infrastructure provided by the library, and identify collections of library materials that are frequently used by users. The reason is to fulfill one of the project assignments for the Monitoring and Evaluation course. The research method used is qualitative. by using an instrument technique or an online questionnaire form. This is because the researcher does not have time to go to the desired place of observation other than to do various things. Researchers will collect participants according to the respondent's subject specified in the previous report, especially to the librarian in collecting data. The research place that is the focus of research is the university library. Participant observation and field research are examples of ethnographic techniques that can be used. As a result, the authors were able to obtain data and information from the head of the library and librarian, in addition to drawing conclusions about problems and solutions from the data collected, and finally getting information about the satisfaction of users who have used the library using the EUCS model.